Effects of Indonesian marine sponges ethanol extracts on the lipid profile of hyperlipidemic rats - Wahyuni Wahyuni, Adryan Fristiohady, Muhammad Hajrul Malaka, Fadhliyah Malik, Muhammad Ilyas Yusuf, Mesi Leorita, Baru Sadarun, Ahmad Saleh, Wa Ode Sitti Musnina, Carla W. Sabandar, Idin Sahidin (Journal of Applied Pharmaceutical Science, 2019)
This study was aimed to investigate the effects of ethanol extracts of Indonesian marine sponges (Callyspongia sp., Melophlus sarasinorum, and Xestospongia sp.) on the lipid profile of hyperlipidemic rats. The antihyperlipidemic study of these sponges is firstly reported in this study. Experimental hyperlipidemic rats were induced by daily intake of propylthiouracil (1.8 mg/200 g b.wt and quail yolk (10 ml/kg) for the duration of 3 weeks. Hyperlipidemic rat groups were administered orally with three doses (30, 60, and 120 mg/kg) of the ethanol extracts for 1-week onward. Blood sample was then collected via intracardiac puncture and serum was biochemically analyzed. Ethanol extracts of Callyspongia sp., M. sarasinorum, and Xestospongia sp. at doses of 60 and 120 mg/kg exhibited a significant reduction of cholesterols, triglycerides, and low-density lipoprotein. These doses also significantly increased the highdensity lipoprotein level. Levels of atherogenic indices (Atherogenic Index, Atherogenic Index Plasma, Castelli’s Risk Index-I, and Castelli’s Risk Index-II) were also decreased by both doses with percentages protection ranging from 70.6% to 81.6%. These results showed that ethanol extracts of Callyspongia sp., M. sarasinorum, and Xestospongia sp. exhibited a lipid-lowering activity in hyperlipidemic rats. Hence, these extracts could be used as sources of lead molecules in the development of natural lipid-lowering agents from marine species.
Keywords: Antihyperlipidemia, marine sponge, Callyspongia sp., Melophlus sarasinorum, Xestospongia sp.